(untitled) (Bangladesh Medical Journal, 2016)
Smoking may cause atherosclerosis and acute cardiovascular events and hyperhomocystenemia may found in smokers that play a vital role in development of atherosclerosis and acute cardiovascular events. The present cross sectional study was carried out in the Department of Physiology, Dhaka Medical College, Dhaka between July 2013 to June 2014 to assess the serum homocysteine (Hcy) level in male smokers. A total number of 200 male subjects were selected with age ranging from 20 to 40 years. Among them, 100 male smokers were included in the study group (Group B) and 100 male non-smokers of same age ranging were considered as controls (Group A). Detailed smoking and medical history was taken regarding drug intake and general examinations were done. The mean serum homocysteine level was significantly higher in adult male smoker than that of adult male non smoker (p < 0.001). This study concludes that serum homocysteine level increases in male smokers which may act as risk factor for future cardiovascular diseases and atherosclerosis. Bangladesh Med J. 2016 May; 45 (2): 72-74